2020
DOI: 10.1016/j.xphs.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thermosensitive Polymer-Modified Liposomes as Nano-Carrier of Hydrophobic Antitumor Drugs

Abstract: Thermo-sensitive polymer-modified liposomes are able to achieve site-specific delivery of drugs. In this work, thermo-sensitive polymers were synthesized by atomic transfer radical polymerization of N-isopropyl acrylamide (NIPAAm) and N,N-dimethyl acrylamide (DMAAm) using bromoisobutyryl distearoyl phosphoethanolamine (DSPE-Br) as initiator. The resulting PNIPAAm-DSPE and P(NIPAAm-DMAAm)-DSPE polymers were characterized using proton nuclear magnetic resonance, Fourier transform infrared, and ultraviolet-visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…These acoustic waves are applied as a release mechanism through cavitation which enhances the accumulation of anticancer drugs at the tumor site [101]. Recently, Xi et al, 2020, reported polymer-modified thermoresponsive liposomes (TSL) from utilizing a lipophilic anticancer chemotherapeutic agent for the treatment of cancer from TSLs [102]. This study reflects that this technology could be exploited for delivery of the challenging anticancer drugs using liposomal preparations.…”
Section: Ultrasound-responsive Drug Delivery Systems (Urdds)mentioning
confidence: 97%
“…These acoustic waves are applied as a release mechanism through cavitation which enhances the accumulation of anticancer drugs at the tumor site [101]. Recently, Xi et al, 2020, reported polymer-modified thermoresponsive liposomes (TSL) from utilizing a lipophilic anticancer chemotherapeutic agent for the treatment of cancer from TSLs [102]. This study reflects that this technology could be exploited for delivery of the challenging anticancer drugs using liposomal preparations.…”
Section: Ultrasound-responsive Drug Delivery Systems (Urdds)mentioning
confidence: 97%
“…Smart drug delivery systems using temperature‐responsive polymers are ideal for targeted delivery or controlled drug release. [ 28,29 ] Modification of nanocarriers with PNIPAAm derivatives can alter the LCST, leading to a more flexible nanoparticle tailored to its application, whether the aim is for the prolonged, burst, or sustained release of drugs. [ 29,30 ] Examples of nanocarriers that have been widely studied and well‐established are liposomes, micelles, and polymeric nanoparticles.…”
Section: Pnipaam Applications In Drug Delivery Systemsmentioning
confidence: 99%
“…The PTSL showed low cytotoxicity while carrying the drug. They reduced the viability of A549 lung cancer cells ( Xi et al, 2020 ).…”
Section: Liposomes For Delivery Of Therapeutic and Imaging Agentsmentioning
confidence: 99%